'Halo-kinematic' sequence-stratigraphic analysis of minibasins in the deepwater contractional province of the Liguro-Provençal basin, Western Mediterranean. (June 2020) - Mianaekere, V.; Adam, J.
Abstract: This study investigates the co-evolution of gravity-driven thin-skinned salt tectonic processes and minibasin-scale halokinetic-depositional processes for the kinematic analysis of salt diapirs in the diapiric province of the contractional domain of the deepwater Liguro-Provençal Basin. We apply minibasin-scale halo-kinematic sequence-stratigraphic concepts to investigate local controls of diapir growth and creation of accommodation space in related salt-withdrawal minibasins. Halokinetic wheeler diagrams extrapolated from 2D interpretation of geo-seismic sections show local temporal halokinetic processes of periods of ponding and styles of near diapir erosion or slumping. Structurally restored 2D minibasin sections along with derived structural wheeler diagrams show a typical syn-kinematic cycle of events consisting of ponding, flap folding and erosion within minibasin sediment successions. Structural wheeler diagrams demonstrate the structural transition from large length scale (100's of meters to several kilometers) folding above diapir pedestals to small length scale (10's of meters) folding proximal to steep diapir flanks. Large length scale folds are associated with early pre-kinematic layers; they mechanically rotate around the minibasin center. Small length scale folds are associated with younger depositional sequences; they rotate around local depocentre focus points. Highlights: The Co-evolution of gravity-driven thin-skinned salt tectonic processes and minibasin-scale halokinetic-depositional sequences. Kinematic analysis of salt growth and creation of accommodation space in related salt-withdrawal minibasins. Stratigraphic spatial-temporal changes in depositional patterns are regarded with structural flap folding of stratal layers within minibasins. New methods introduced are halokinetic wheeler and structural wheeler diagrams. Halokinetic wheeler diagrams show local temporal halokinetic processes. Structural wheeler diagrams show the stratigraphic syn-kinematic cycle of combined halokinetic and structural events.